2017
DOI: 10.3390/vetsci4040067
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Fractional Excretion of Phosphorus in Dogs with Spontaneous Chronic Kidney Disease

Abstract: Abstract:The increase of urinary fractional excretion of phosphorus (uFEP) may indicate phosphorus retention before the onset of hyperphosphatemia in the early stages of chronic kidney disease (CKD). The hypothesis of this study is whether uFEP may increase during the early stage of CKD as a compensatory mechanism to prevent hyperphosphatemia as well as whether hyperphosphatemia in the late stages is associated with increase or decrease in uFEP in dogs with naturally occurring CKD; therefore, the aim of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
(68 reference statements)
0
6
1
1
Order By: Relevance
“…However, uFEP was not identified as an independent predictor of FGF-23 in our multivariable analysis. A previous study has shown that uFEP was similar between CKD dogs with IRIS stage 3 and 4 (Martorelli et al 2017). In our study, while there was no significant difference between dogs with IRIS stages 2-4 for uFEP, FGF-23 progressively increased in dogs with CKD, even at the later stage.…”
Section: Discussioncontrasting
confidence: 46%
“…However, uFEP was not identified as an independent predictor of FGF-23 in our multivariable analysis. A previous study has shown that uFEP was similar between CKD dogs with IRIS stage 3 and 4 (Martorelli et al 2017). In our study, while there was no significant difference between dogs with IRIS stages 2-4 for uFEP, FGF-23 progressively increased in dogs with CKD, even at the later stage.…”
Section: Discussioncontrasting
confidence: 46%
“…In chronic renal disease, which is common in CanL, anemia also results from decreased erythropoietin production in the kidney [8,48]. Kidneys are the main route for phosphorus excretion and hyperphosphatemia promotes progressive renal lesions [49], as described in dogs with late-stage CanL [50]. Serum globulin and acute phase proteins levels, proteinuria and UPC ratio are considered biomarkers for the clinical monitoring of dogs during leishmanicidal treatment and post-treatment [3,17,18,51,52].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, urinary qualitative proteinuria and electrolytes urinary fractional excretion have been considered in the assessment of renal damage [ 7 , 50 ]. Specifically, qualitative proteinuria and proteomics allow the analysis of biomarkers indicative of kidney damage such as cauxin, uromodulin, and retinol binding protein [ 50 , 51 , 52 ].…”
Section: Femv As the Causative Agent Of Renal Disease?mentioning
confidence: 99%